(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2009)
As part of the Knowledge Management be find include one aspect of high relevance not only accounting, but also productive and competitive, which is called today Intellectual Capital (IC), thus this document gives an account of bibliographic definitions and models known more about it through the literature collection coming to establish a model and some relevant indicators in the role of Colombian industry.